2014
DOI: 10.1530/eje-13-0455
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between circulating estradiol and thyroid autoimmunity in males

Abstract: Introduction: Although autoimmune thyroid disease is less common in males, it is unclear whether estrogen contributes to the difference in susceptibility among males. Objective: To examine whether circulating estradiol (E 2 ) is related to thyroid autoimmunity in males. Patients and methods: One-thousand two-hundred and sixty-three males aged 15-94 years were studied. Serum levels of E 2 , TSH receptor antibody (TRAb), thyroid peroxidase antibody (TPOAb), thyroglobulin antibody (TgAb), free thyroxine (FT 4 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…We previously reported a negative association between serum BPA and serum thyroxine (T4) in males with positive serum thyroid antibodies [6] which is in agreement with a recent study in U.S. adults which suggested an inverse relationship between urinary BPA and total T4 [7]. Moreover, we have also demonstrated that estradiol is associated with thyroid autoimmunity in males [8]. The three most important antigens in autoimmune thyroid disease are thyroglobulin, thyroid peroxidase and TSH receptor.…”
Section: Introductionsupporting
confidence: 88%
“…We previously reported a negative association between serum BPA and serum thyroxine (T4) in males with positive serum thyroid antibodies [6] which is in agreement with a recent study in U.S. adults which suggested an inverse relationship between urinary BPA and total T4 [7]. Moreover, we have also demonstrated that estradiol is associated with thyroid autoimmunity in males [8]. The three most important antigens in autoimmune thyroid disease are thyroglobulin, thyroid peroxidase and TSH receptor.…”
Section: Introductionsupporting
confidence: 88%
“…For example, X-chromosome inactivation has been associated with autoimmune thyroid disease (40). However, there have been reports in men that confirm a connection between estradiol levels (or estradiol to testosterone ratio) and thyroid autoimmunity (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens influenced B-cell function and further regulated the immune system [36]. In GD patients, the increased estradiol level is related to the positivity of TRAb [37]. Although the incidence of GD is higher in women, male GD patients have a higher risk of recurrence after ATD withdrawal [6, 34, 38, 39].…”
Section: Influencing Factors For the Recurrence In Gd Patientsmentioning
confidence: 99%